Equation of state for dense gases from a self-consistent-field approach in the framework of kinetic theory. Issue 1 (2nd January 2020) - Giusti, D.; Molinari, V.; Mostacci, D.
ABSTRACT: The departure from ideal gas behavior is described by several known equations of state (EoS), developed from a combination of theoretical considerations and experimental correlations. In this work, a different approach, in the framework of kinetic theory, is proposed: from a pairwise potential of the Lennard–Jones type, the interaction between molecules is accounted for by means of a self-consistent force field. The propagation of a perturbation wave in the dense gas or liquid of unperturbed density n 0 is described and the isothermal propagation velocity is determined. An EoS is derived and compared to the van der Waals EoS, of which it is found to reproduce the main features.